On accurate characterization of interfacial morphology and damage evolution of thermoplastic composite welded joints: A microscale study via in-situ micro-CT. (3rd May 2023) - Zhao, Quanyue; Gao, Zhuqing; Wang, Hongen; Wu, Hantai; Chen, Xinyu; Qu, Zhaoliang; Zhao, Tian; Fang, Daining
Abstract: Thermoplastic composites are regarded as a potential alternative to their thermoset counterparts in aircraft industries owing to their cost-effective manufacturing process and weldability. However, one of the most significant limitations of the currently used evaluation methods for the welded joints is that they are mostly destructive, which makes the loss of information on the initial features of the welding interface. In this study, the interfacial morphology and damage evolution of ultrasonic welded GF/PPS thermoplastic composite joints were accurately characterized by using in-situ micro-CT technique. The morphology of the weldline was demonstrated by the evolution of void defects, fibre architecture and resin contents of specimens created using different sonotrode travels. Based on that, the damage evolution scenario of the specimens welded at 40% and 100% travels was successively analysed via in-situ micro-CT analysis. In the final part, the newly proposed technique was comparatively discussed with the traditional characterization methods. Graphical abstract: Image 1 Highlights: In-situ X-ray CT technique was used to characterize the interfacial morphology and damage evolution at the welding interface. Both scale and quantity of the void defects were significantly decreased as the welding travel increasing. Damage evolution within the welding interface was successfully monitored via the in-situ tests.